Life cycle assessment of additively manufactured elastocaloric Ni-Ti heat pump/refrigeration components and the effect of design geometry on the environmental impact categories - Anesu Nyabadza; Karthikeyan Tamil; Lehar Asip Khan; Sujith S. Kumar; Corné Muilwijk; Greg McNamara; Kevin O'Toole; Lorna Fitzsimons; Dermot Brabazon (Results in Engineering)
Elastocaloric Ni-Ti alloys offer solid-state heat pump and cooling applications. The environmental impact of elastocaloric Ni-Ti parts manufactured via powder bed fusion was assessed using life cycle assessment with the ReCiPe method. These solid-state heat pumps can mitigate the environmental impacts of current air conditioning/refrigeration methods that use harmful chemicals like CFCs, HCFCs, and HFCs. Measurements of electricity, Ar gas, and compressed air consumption were considered within the gate-to-gate boundary, covering powder transportation, printing, and use-phase. Nickel was identified as the most damaging input, reducible through geometry optimization. Optimized geometries (given the same number of printing layers) require more energy during powder bed fusion however, the environmental benefit from material saving outweighs the damage from increased electrical usage by far. The powder bed fusion machine's standby mode consumes more energy and Ar gas than the printing process, presenting an opportunity for mitigation. Additively manufactured Ni-Ti elastocaloric structures were used as heat generators/sinks in flowing water during compression cycles, achieving 11 °C and 10 °C water temperature change per cycle for the solid geometry and the optimized geometry respectively. A 10 x 10 × 55 mm Ni-Ti structure, providing >2 °C temperature span under compressive cycles, served as the functional unit.